Marine Ecological Governance Under New Media Environment: Tripartite Evolutionary Game and Simulation Analysis - Gao, Lehua; Yan, An; Yin, Qiaorong (Frontiers in Environmental Science, 2022)
Based on the general reality that new media with massive information and strong interaction play an increasingly prominent role in marine ecological governance, this study introduces the coastal public participation mechanism under the new media environment. Furthermore, it analyzes the impact of certain factors on the strategy selection of governance subjects by constructing an evolutionary game model among local governments, marine enterprises, and coastal public. These factors include the influence and accuracy of new media reports. Combined with the data from a questionnaire survey conducted in 14 coastal cities in China, numerical simulation is then conducted. The research demonstrates the following. (1) An objective and fair new media environment exerts a positive guiding effect on marine ecological governance, whereas a false and distorted one will lead to chaos in marine ecological governance. (2) Considering the high accuracy of new media reports, the higher the sensitivity of the local governments and marine enterprises to media reports is, the more inclined they are toward strong regulation and active governance. (3) The local governments can effectively restrain the marine hazard behavior of the marine enterprises by increasing penalties and environmental protection taxes, and it is equally important to guide marine enterprises to fully utilize high and new technology in the marine industry for improving economic benefits and reducing governance costs. (4) Coastal public participation can effectively compensate for the local governments’ regulatory loopholes and can reduce the cost of government regulation. Therefore, for ensuring objective reports of new media by establishing reward and punishment mechanisms and regularly selecting excellent new media, using new media to enhance the level of marine publicity and education to encourage coastal public to widely and fully participate in marine ecological governance is an effective means.